1999
DOI: 10.1093/bja/82.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopexamine on blood flow in multiple splanchnic sites measured by laser Doppler velocimetry in rabbits undergoing cardiopulmonary bypass

Abstract: Decreased gut perfusion has been reported during cardiopulmonary bypass (CPB). Studies of treatments to avoid splanchnic ischaemia during CPB have given conflicting results. We studied 12 rabbits during mild hypothermic non-pulsatile CPB. Tissue blood flow in three different splanchnic areas (gastric, jejunum and ileum) was measured by laser Doppler velocimetry (LDV) before CPB (T0), after steady state (T1), after administration of dopexamine 2 micrograms kg-1 min-1 (T2) and 4 micrograms kg-1 min-1 (T3), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…The administration of dopexamine significantly increased IMBF at all measurement times. Similar increases in IMBF, measured using LDF, during dopexamine administration have been demonstrated in other experimental and clinical settings [17-19]. In a mild hypothermic cardiopulmonary bypass model in rabbits, dopexamine significantly increased jejunum and ileum blood flow, estimated using LDF [17].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The administration of dopexamine significantly increased IMBF at all measurement times. Similar increases in IMBF, measured using LDF, during dopexamine administration have been demonstrated in other experimental and clinical settings [17-19]. In a mild hypothermic cardiopulmonary bypass model in rabbits, dopexamine significantly increased jejunum and ileum blood flow, estimated using LDF [17].…”
Section: Discussionsupporting
confidence: 60%
“…Similar increases in IMBF, measured using LDF, during dopexamine administration have been demonstrated in other experimental and clinical settings [17-19]. In a mild hypothermic cardiopulmonary bypass model in rabbits, dopexamine significantly increased jejunum and ileum blood flow, estimated using LDF [17]. In an experimental setting in pigs, jejunal mucosal blood flow was not influenced by dopexamine infusion during intestinal hypotension, but dopexamine brought about intestinal vasodilatation [10].…”
Section: Discussionmentioning
confidence: 60%
“…Since they are supplied by end-arteries, it is likely that the tip of villi is particularly sensitive to ischemia. In animal models of CPB, blood flow to the jejunal and ileal mucosa during CPB is about one third of pre-CPB blood flow [14,15]. However, these changes have not been documented clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Splanchnic blood flow was found decreased during cardiac shock and cardiopulmonary bypass (CBP) as well [22,23]. Measurements in different splanchnic areas of a rabbit model indicated that the prophylactic use of dopexamine protected jejunum and ileum blood flow but not gastric perfusion [24]. These findings might explain the conflicting results with respect to the effect of the drug on gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%